Electrophysiological indexes of the cognitive-motor trade-off associated with motor response complexity in a cognitive task - Bianca Maria di Bello; Andrea Casella; Merve Aydin; Stefania Lucia; Francesco Di Russo; Sabrina Pitzalis (NeuroImage)
Complex actions require more cognitive and motor control than simple ones. Literature shows that to face complexity, the brain must make a compromise between available resources usually giving priority to motor control. However, literature has minimally explored the effect of the motor response complexity on brain processing associated with cognitive tasks. Consequently, it is unknown whether carrying out a cognitive task requiring motor responses of increasing complexity could reduce cognitive processing keeping stable motor control. Therefore, this study aims to investigate possible modulations exerted by increasing motor response complexity in a cognitive task on brain processing. To this aim, we analyzed the event-related potentials and behavioral responses during a cognitive task with increasing complexity of the required motor response (keypress, reaching and stepping). Results showed the increasing motor complexity enhances early visual and attentional processing (P1 and N1 components) but reduces the late post-perceptual cognitive control (P3 component). Additionally, we found a component following the P3 which was specific for stimuli requiring a response. This component, labeled N750, increased amplitude along with the response motor complexity. Behaviorally, response accuracy was not affected by complexity. Results indicated that in cognitive tasks stimulus processing is affected by the complexity of the motor response. Complex responses require a greater investment of early perceptual and attentional resources, but at late phases of processing, cognitive resources are less available in favor of motor resources. This confirms the idea of the motor-priority cognitive-motor trade-off of the brain.